Renal function to 5 years after late conversion of kidney transplant patients to everolimus: a randomized trial - Budde, Klemens; Sommerer, Claudia (Journal of nephrology, 2015)
BackgroundFew trials have investigated late preemptive conversion of kidney transplant patients from a calcineurin inhibitor (CNI) to an mTOR inhibitor.MethodsIn an open-label, 12-month, prospective, randomized, parallel-group study, maintenance kidney transplant patients (>6 months post-transplant) either switched from CNI to everolimus or continued their current CNI regimen. Patients who completed the core study were followed to 5 years post-randomization.ResultsOf 93 randomized patients, 78 completed the core study and 67 attended the final 60-month study visit. Mean time post-transplant at baseline was 82.6 months and 70.5 months in the everolimus and CNI groups, respectively. At month 60, adjusted mean eGFR (Nankivell) was 63.0 (95 % CI 57.8, 68.2) mL/min/1.73 m2 in the everolimus group versus 57.9 (95 % CI 52.6, 63.1) mL/min/1.73 m2 in the CNI group, a difference of 5.1 (95 % CI −0.6, 10.8) mL/min/1.73 m2 (p = 0.076). Among patients who remained on randomized study drug at month 60, mean eGFR (Nankivell) was 71.6 (95 % CI 64.2, 79.0) mL/min/1.73 m2 in everolimus-treated patients (n = 21) versus 60.6 (95 % CI 55.1, 66.1) mL/min/1.73 m2 in CNI-treated patients (n = 29) (mean difference 11.0; 95 % CI 3.6, 18.5 mL/min/1.73 m2; p = 0.005). No cases of BPAR occurred from randomization to month 60 in either group. Graft loss occurred in three everolimus-treated patients and one CNI-treated patient. No unexpected safety concerns were observed in either group.ConclusionLate preemptive conversion of maintenance kidney transplant patients from CNI to everolimus may be associated with improved long-term renal function and preserves immunosuppressive efficacy. Patient numbers were low, but these findings merit further investigation.